The impact of COVID-19 on audit fees and audit report lag: Evidence from Malaysian Islamic Banks - Uyob, Suzilawati; Othman, Jaizah; Abd Ghani, Nur Amalina; Md Zin, Ana Salwa; Ramli, Junaira; Salleh, Kalsom (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2022)
The world is currently dealing with a severe health, economic, and social crisis brought on by the coronavirus disease of 2019 (COVID-19), which has spread quickly. Globally, the COVID-19 epidemic has already had a significant negative impact on the economy and finances. This study investigates the effect of Pandemic COVID-19 on audit fees, audit quality and audit report lag. This study observes the annual reports of 16 Malaysian Islamic from 2016 to 2020. A panel data analysis is used for hypothesis testing. The study found that Islamic banks in Malaysia needed a longer time to issue audit reports during the Covid-19 crisis than before the crisis. However, audit fees and quality are not affected by the Covid-19 crisis. This study is only on data from Licensed Islamic banks in Malaysia. Therefore, this study cannot be generalised to the entire economy of Malaysia.This study is helpful for future researchers in contributing literature to their study and helpful for policymakers to be better prepared to face the risk of future crises.